Methods for the Fast Detection of Unpleasant Odorants and Other Non-intentionally Added Substances in Recyclates - Gomes de Aragao Belé, Tiago; Haug, Helen; Sauerwald, Tilman (Springer Handbook of Circular Plastics Economy, 2025)
This chapter will give an insight into analytical systems for the detection of odorants and other volatile compounds in recyclates. In this field, comprehensive, yet very time-consuming, offline analytical methods for sampling, chromatographic separation, identification, and quantification include, for example, solvent extraction, (two-dimensional) gas chromatography (GC) coupled with high-resolution mass spectrometry (MS), and flame ionization detection (FID). They serve as a gold standard for the identification and quantification of volatiles and can be complemented with elaborate olfactometric investigations through GC-olfactometry (GC-O) analysis using aroma extraction dilution analysis (AEDA) to describe each odorant quantitatively. However, not all applications require a complete identification of all components and therefore, a different approach may need to be chosen. For established methods for volatiles and odorants analysis, most steps require extensive manual work in sample preparation, measurement, and data processing. Due to its high effort, offline character and time consumption, there is a thrive for faster and less expensive methods and instrumentation in every aspect. Starting from the perspective of recyclate quality monitoring in a circular economy and its specific challenges and needs, we try to give an overview into established as well as promising upcoming methods. This includes different aspects of sample preparation, instrumentation as well as strategies for the automation of lab work and data evaluation. It should serve as an easy access to this complex topic and provide a broad overview and hints as for a deeper dive into this topic.
CRIS-Team Scopus Importer:2025-07-18
Keywords: Gas chromatography-mass spectrometry; Non-intentionally added substances; Odor analysis; Odorants; Olfactometry; Recyclate quality monitoring; Smart odor assessment